Hop as a phytogenic alternative to antibiotic growth promoters in poultry production - Kober, Luisa; Strauch, Sebastian M.; Schwab, Stefan; Becker, Anna; Erzinger, Gilmar S.; Castiglione, Kathrin (Journal of the Science of Food and Agriculture, 2024)
With the rapid growth of the world's population, the demand for food is also increasing. Poultry accounts for 40% of the global meat sector and therefore represents a significant area for further growth. One starting point for increasing production is to refine the composition of feed to improve the efficiency of growth and nutrient utilization, prevent disease and at the same time reduce environmental impact. Similar considerations have led to the long-standing sub-therapeutic use of antibiotics as growth promoters in animal husbandry, which is associated with the threat of rising antimicrobial resistances and the resulting consequences for human and animal health. In order to circumvent these drawbacks, an increasing number of alternative feed additives are becoming more prevalent. The use of phytogenic feed additives, which includes hops (Humulus lupulus), is regarded as a viable alternative. In addition to its natural availability, hops have been demonstrated to exhibit antimicrobial effects and there is increasing evidence of growth-promoting effects in vivo. © 2024 The Author(s). Journal of the Science of Food and Agriculture published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.
CRIS-Team Scopus Importer:2024-10-11
Keywords: antibiotic resistance; antimicrobials; feed additives; Humulus lupulus; phytogenics